The benchmarking of opposite player: comparison between Plus Expressways and Abertis Spain / Hafizah Zuraipah Asliza Hassan - Hassan, Hafizah Zuraipah Asliza (Faculty of Business and Management, 2010)
This case study exploring the “The benchmarking of opposite player: comparison between Plus Expressways and Abertis, Spain” that implement by Plus Expressways Berhad a subsidiary of United Engineer Malaysia (UEM). This study will help the researcher to gain knowledge about the advantages of benchmarking to company. How far benchmarking is requiring helping company to successful in future. This study will help the researcher to gain knowledge about the advantages of benchmarking to company. How far benchmarking is requiring helping company to successful in future. This study also provides the understanding of the activities done to grab the business opportunities via benchmarking steps.